Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina - Vieira, Rodrigo; Landa, José Manuel Ayala; Rafael, José Albertino (Zootaxa, 2017)
Ctenodontina Enderlein is reported for the first time in Argentina. A new species, C. sagta sp. nov. (Argentina, Salta) is described. New combination is Ctenodontina baleta (Walker), comb. nov. with two synonimies: Pachychoeta caracasae Martin syn. nov. and Pachychoeta inca Martin syn. nov. The male and female terminalia of C. baleta (Walker). comb. nov. is illustrated and described for the first time and a key to species is presented.